Science Process Skills Analysis of Science Teacher on Professional Teacher Program in Indonesia (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The low level of science teacher graduation in the professional teacher program in the last two years has become a severe concern for researchers in higher education. Here we analyze these problems by measuring the Science Process (SP) Skills of science teachers in Indonesia through this program. Data collection procedures are interviews, worksheets, and questionnaires, while data analysis techniques use mixed methods, consist of quantitative and qualitative methods simultaneously. The SP skills data obtained were Observing 76.1%, Proposing Hypothesis 76.4%, Planning an Experiment 60.0%, Utilizing Tools 57.2%, Interpreting 39.4%, Applying Concept 48.1%, and Communicating 18.3%. The lowest percentage is in interpreting skills and communicating skills. Based on the analysis result, the causes are the short time teaching experience and the educational background of science teachers who are not linear with their competence.